백출과 양춘사 추출 혼합물의 항콜레스테롤 효과 및 기전 연구 - 김하림(Ha Rim Kim); 김예슬(Ye Seul Kim); 권강범(Kang Beom Kwon); 정현종(Hyun Jong Jung) (동의생리병리학회지, 2022)
Atractylodes macrocephala (AM) and Amomum villosum (AV) are the most common herbs in Korean Medicine to treat digestive diseases. In this study, we investigated the cholesterol lowering effects of mixtures of AM and AV extracts on high cholesterol diet (HCD) induced dyslipidemia mouse model. We classified animals into six different groups; Group 1: Normal diet, Group 2: HCD, Group 3: AV extracts : AM extracts (1:1) (200 mg/kg) + HCD, Group 4: AV extracts : AM extracts (1:2) (200 mg/kg) + HCD, Group 5: AV extracts : AM extracts (1:3) (200 mg/kg) + HCD, Group 6: Simvastatin 40 mg/kg + HCD. After 4 weeks of oral administration of respective drugs, we checked body, liver and epididymal fatweights along with liver and serum triacylglyceride (TG) concentration, total and low density lipoprotein (LDL) cholesterol in serum. Moreover, 3-hydroxy-3-methylglutaryl-CoA (HMG-CoA) reductase (HMGCR), LDL receptor (LDLR), and sterol regulatory element-binding protein 2 (SREBP2) were detected by RT PCR or western blot analysis. The overall results showed that mixtures of AM and AV extracts inhibited HCD-induced increases of total cholesterol and LDL cholesterol in serum. Those effects seem to be caused by AM and AV extracts through inhibition of HMGCR expression. And thus blood cholesterol is induced into the liver by increasing LDLR expression, which is regulated by SREBP2 transcrption factor. The cholesterol lowering effects and mechanism of mixtures of AM and AV extracts was similar to the statin. We have identified the potential mixtures of AM and AV extracts as a new treatment for dyslipidemia.